Open Data as a Strategic Resource for Enterprises - Systematic literature review - Blatnik, Staša; Pucihar, Andreja; Čelik, Nejc; Lenart, Gregor (Odprti podatki kot pospeševalec družbenih, okoljskih in gospodarskih inovacij – priložnosti in izzivi, 2026)
To remain competitive in the market, companies must continuously evolve and adapt to increasingly specific customer needs. One of the resources that can stimulate business activity and innovation is open data. Through a systematic literature review on the use of open data in companies, we identified key scientific publications, which we classified into eight thematic areas: models, value creation, drivers and barriers, users, data quality, portals, research classifications, and the impact of open data. The findings show that research emphasizes the potential of open data for innovation, process optimization, transparency, and the development of new business models, while also highlighting challenges such as low data quality, lack of standardization, fragmented sources, and limited organizational capacities. Despite proven positive effects on the economy and democratic processes, the question remains of how to systematically encourage the actual use of open data. Further research will be crucial for developing practical and theoretical guidelines that enable companies to better leverage this business potential, for which this study provides a fundamental theoretical basis.